The Relevance of the MCP Risk Polymorphism to the Outcome of aHUS Associated With C3 Mutations. A Case Report - Lumbreras, Javier; Subias, Marta; Espinosa, Natalia; Ferrer, Juana María; Arjona, Emilia; Rodríguez de Córdoba, Santiago (Frontiers in Immunology, 2020)
Thrombotic microangiopathy (TMA) has different etiological causes, and not all of them are well understood. In atypical hemolytic uremic syndrome (aHUS), the TMA is caused by the complement dysregulation associated with pathogenic mutations in complement components and its regulators. Here, we describe a pediatric patient with aHUS in whom the relatively benign course of the disease confused the initial diagnosis. A previously healthy 8-year-old boy developed jaundice, hematuria, hemolytic anemia, thrombopenia, and mild acute kidney injury (AKI) in the context of a diarrhea without hypertension nor oliguria. Spontaneous and complete recovery was observed from the third day of admission. Persistent low C3 plasma levels after recovery raised the suspicion for aHUS, which prompted clinicians to discard the initial diagnosis of Shigatoxin-associated HUS (STEC-HUS). A thorough genetic and molecular study of the complement revealed the presence of an isolated novel pathogenic C3 mutation. The relatively benign clinical course of the disease as well as the finding of a de novo pathogenic C3 mutation are remarkable aspects of this case. The data are discussed to illustrate the benefits of identifying the TMA etiological factor and the relevant contribution of the MCP aHUS risk polymorphism to the disease severity.